2016
DOI: 10.1177/2396939316656323
|View full text |Cite
|
Sign up to set email alerts
|

Church Planting and Church Growth in Western Europe: An Analysis

Abstract: Church planting is often seen as the best way to grow the church numerically. However, there is surprisingly little research examining this claim in any detail, and the research that exists turns out to be not very well-founded or unclear in terms of sources, definitions, and so forth. Recently, research has been conducted in three small Reformed denominations in the Netherlands, comparing older and younger churches with regard to converts and returnees. The results show that the younger churches gained approx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…However, this research, although conducted with scientific rigor and based on fairly accurate data, works with very unequal sample sizes: only 16 church plants against 476 older churches, of which, respectively, 13 and 143 (response rates of 81 and 30 percent) participated in the research. 4 Nevertheless, this is in fact the only research project in Europe that is based on solid data, and it presents transparent outcomes as regards the relationship between church planting and church growth.…”
mentioning
confidence: 99%
“…However, this research, although conducted with scientific rigor and based on fairly accurate data, works with very unequal sample sizes: only 16 church plants against 476 older churches, of which, respectively, 13 and 143 (response rates of 81 and 30 percent) participated in the research. 4 Nevertheless, this is in fact the only research project in Europe that is based on solid data, and it presents transparent outcomes as regards the relationship between church planting and church growth.…”
mentioning
confidence: 99%
“…This disconnection of relationships after people leave the church creates barriers against inviting them to return. The data and existing literature also demonstrate that dechurched Christians may have left with favorable and/or unfavorable feelings about their church experience (Paas and Vos 2016). The qualitative findings point us to participants’ best memories of love and community, and the understanding and companionship they long to experience in church.…”
Section: Resultsmentioning
confidence: 63%
“…These welcoming settings encourage people who are churched, dechurched, or unchurched to come together to make sense out of life and be nourished by the welcome and friendship that more intimate church groups can offer. Furthermore, new church plants or newly formed Christian communities are also found to be effective in reaching the dechurched (Paas and Vos 2016).…”
Section: Helping Dechurched Christians To Belong and Grow Spirituallymentioning
confidence: 99%
“…Our city-based samples showed that the eleven BFeG-churches in Berlin experienced strong net conversion growth (conversion minus decline), and that the Berlin sample in fact was the only BFeG sample with a positive net conversion growth. Other research shows that actual investment in evangelism (rather than missional rhetoric or beliefs) are good predictors of recruitment success (Paas & Vos 2016). This may be in better supply in newer churches, as they are more often led by entrepreneurial leaders (Boy 2015, 108-118;Foppen et al 2018).…”
Section: Discussionmentioning
confidence: 99%